FAULT TOLERANT DIGITAL CONTROLLER FOR DC-DC SWITCHING POWER CONVERTER USING MODULAR REDUNDANCY - Dilbie, Daniel (Zede Journal of Ethiopian Engineers and Architects, 2023)
Power converters and regulators are the main and critical building blocks of all electronic systems. In applications prone to transient faults, such as particle strikes, spatial redundancy techniques can improve the reliability significantly. The design of a fully digital DC/DC switching buck converter regulator based on a fault tolerant modular redundancy architecture implemented on SRAM FPGAs is presented. Transient events such as single event functional interrupts (SEFIs) are the dominant effects in SRAM-based FPGAs. SEFIs result in missing pulses in the generated PWM control signal of the converter that cause large transient drops at the converter output. In this work, triple modular redundancy (TMR) technique is used to implement spatial redundancy. This approach is used to triplicate the physical digital blocks on FPGA such that faults on one of the modules can be detected and corrected while the system works uninterrupted and with correct output. Experimental results indicate that with triple modular redundancy, the power converter can withstand up to 5x more doze of faults as compared to conventional power converters. Key words: single event functional interrupt (SEFI), fault tolerant design, spatial redundancy, DC/DC switching power converter, buck converter, digital control